Teacher preparation in ireland - O'Donoghue, T. A. (Tom A.), 1953-; Harford, Judith; O'Doherty, Teresa (Bingley, U.K. : Emerald Publishing Limited, 2017)
Fifty years ago, in 1967, free education was introduced in Ireland for attendance at second-level schools and expansion of provision of education at both this and third-level followed. Currently, great interest is developing in this landmark development in Irish history, which was probably the most significant initiative taken in regard to education in Ireland from Independence from Britain in 1922 to the present. This book contributes to the interest generated by this landmark anniversary by tracing the history of teacher preparation in Ireland. It relates to the introduction the 'free education' education scheme introduced in 1967, in that it provides an exposition on the nature of teacher preparation for teaching in primary and second-level schools both before and after the initiative was taken. Thus, it traces the history of teacher preparation through a number of stages; from education for nation-building in the new post-colonial society to partaking in the recent neo-liberal agenda sweeping through education systems throughout the world. This book should be of interest not only to Irish educationists, historians and policy makers, but also to their counterparts internationally, as well as to comparative educationists. It can be seen as providing an exposition which can be used by teacher educators in many parts of the world which they can use to sharpen their perceptions of their own situations through comparison and contrast, provoke ideas for critical discussion, and stimulate them to come to an understanding of the importance of considering contemporary developments within their wider historical contexts.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Teachers -- Training of -- Ireland; Teachers -- Training of -- Ireland -- History; Education -- History; History of education